National Trends in Athletic Training Service Provision in U.S. High Schools: A Five-Year Longitudinal Assessment - Kim, D; Eason, Christianne; Grubb, Joseph; Casa, Douglas; Coleman, Kelly; Filep, Erica; Huggins, Robert (Current Sports Medicine Reports, 2026)
Keywords: Athletes; Athletic training; Sports medicine; Trainer; Training (meteorology); dept.hms

Athletic training employment in secondary schools by geographic setting and school size within the United States. - Suzuki-Yamanaka, Miwako; Huggins, Robert A.; Armstrong, Kirk J.; Coleman, Kelly A.; Casa, Douglas J.; Kaneoka, Koji (Journal of athletic training, 2021)
Context: The Athletic Training Locations and Services (ATLAS) Annual Report suggested that athletic trainer (AT) employment status differed based on geographic locale. However, the influence of geographic locale and school size on AT employment is unknown. Objective: To determine if differences existed in the odds of having AT services by locale for public and private schools and by student enrollment for public schools. Design: Cross-sectional study. Setting: Public and private secondary schools with athletics programs. Patients or Other Participants: Data from 20 078 US public and private secondary schools were obtained. Main Outcome Measures(s): Data were collected by the ATLAS Project. Athletic trainer employment status, locale (city, suburban, town, or rural) for public and private schools, and school size category (large, moderate, medium, or small) only for public schools were obtained. The employment status of ATs was examined for each category using odds ratios. Logistic regression analysis produced a prediction model. Results: Of the 19 918 public and private schools with available AT employment status and locale, suburban schools had the highest access to AT services (80.1%) with increased odds compared with rural schools (odds ratio = 3.55 [95% CI = 3.28, 3.85]). Of 15 850 public schools with known AT employment status and student enrollment, large schools had the highest rate of AT services (92.1%) with nearly 18.5 times greater odds (odds ratio = 18.49 [95% CI = 16.20, 21.08]) versus small schools. The logistic model demonstrated that the odds of access to an AT increased by 2.883 times as the school size went up by 1 category. Conclusions: Nationally, suburban schools and large public schools had the greatest access to AT services compared with schools that were in more remote areas and with lower student enrollment. These findings elucidate the geographic locales and student enrollment levels with the highest prevalence of AT services. Ó by the National Athletic Trainers’ Association, Inc
1 citations (Crossref) [2023-10-31] https://www.ncbi.nlm.nih.gov/pubmed/33480996 ; https://pubmed.ncbi.nlm.nih.gov/33480996/ ; https://meridian.allenpress.com/jat/article/56/9/1010/451538/Athletic-Training-Employment-in-US-Secondary ; https://europepmc.org/article/MED/33480996
Keywords: adult; article; athletic trainer; athletics; controlled study; cross-sectional study; dept.hms; employment status; female; high school; human; male; outcome assessment; peer-reviewed; prediction; prevalence; training

Athletic Training Services Trends Between Public and Private High Schools: A 5-Year Retrospective Analysis - Kim, Donghyeon; Defino, Amir; Eason, Christianne; Casa, Douglas; Yoo, Chaeyeon; Yoshihara, Ayami; Coleman, Kelly; Filep, Erica; Huggins, Robert (Journal of Athletic Training, 2025)
Context Access to athletic trainers (ATs) in high schools is crucial for student-athlete (SA) safety. Although most high schools in the United States have access to athletic training services (ATS), no authors have longitudinally compared ATS trends between public (PUB) and private (PVT) school sectors. Objective To compare ATS trends between PUB and PVT schools from the 2018–2019 through 2022–2023 academic years. Design Longitudinal cross-sectional study. Setting Online survey. Main Outcome Measure(s) High school responses to the Athletic Training Locations and Services survey from all 50 US states and the District of Columbia were queried from the 2018–2019 to 2022–2023 academic years. Average numbers of SAs ( SAs ), sports ( Sports ), full-time ATs ( FtATs ), part-time ATs ( PtATs ), and the sum of full-time and part-time ATs ( ATs ), along with the average weekly contracted hours ( CHrs ) and actual hours ( AHrs ) per school, and ratios of SAs : ATs , Sports : ATs , CHrs : SAs , CHrs : Sports , AHrs : SAs , and AHrs : Sports were examined to track ATS trends over 5 years and compare PUB vs PVT schools. Results Public schools had higher SAs and Sports vs PVT schools (both P < .001). Private schools had higher ATs , CHrs , and AHrs than PUB schools (all P < .050). Ratios of SAs : ATs and Sports : ATs were higher in PUB schools, whereas CHrs : SAs , AHrs : SAs , CHrs : Sports , and AHrs : Sports were higher in PVT schools (all P < .050). From 2018–2019 to 2022–2023, PUB schools increased Sports and Sports : ATs ; PVT schools increased SAs , Sports , ATs , and SAs : ATs (all P < .050). Over the years, PUB schools decreased CHrs : Sports and AHrs : Sports ; PVT decreased CHrs : SAs , AHrs : SAs , CHrs : Sports , and AHrs : Sports . FtATs increased in both sectors, whereas PtATs decreased in only PVT schools. Conclusions Overall, ATS were more extensively provided in PVT schools, based on ATs and ATS hours. Both sectors increased FtATs , which is encouraging. However, as SAs and Sports increased, ATS provided per SA and sport declined.
Keywords: Athletes; Athletic training; Context (archaeology); MEDLINE; Private sector; Training (meteorology); athletes; dept.hms; safety; sports; student health services

The effect of high dose creatine supplementation on thermoregulatory adaptation during a standard heat acclimation protocol - Martin, David; Thornton, Staci; Langan, Seam; Navarro, John; Brewer, Gabrielle; Szymanski, Michael; Huggins, Robert; Lunn, William; Rodriguez, Nancy; Casa, Douglas; Lee, Elaine (Medicine & Science in Sports & Exercise, 2025)
Keywords: Acclimatization; Analysis of variance; Core temperature; Creatine; Dehydration; Heat stress; Rectal temperature; Thermoregulation; dept.hms

Establishing a global standard for wearable devices in sport and exercise medicine: Perspectives from academic and industry stakeholders - Ash, Garrett I.; Stults-Kolehmainen, Matthew; Busa, Michael A.; Gaffey, Allison E.; Angeloudis, Konstantinos; Muniz-Pardos, Borja; Gregory, Robert; Huggins, Robert A.; Redeker, Nancy S.; Weinzimer, Stuart A.; Grieco, Lauren A.; Lyden, Kate; et al. (Sports medicine (Auckland, N.Z.), 2021)
Millions of consumer sport and fitness wearables (CSFWs) are used worldwide, and millions of datapoints are generated by each device. Moreover, these numbers are rapidly growing, and they contain a heterogeneity of devices, data types, and contexts for data collection. Companies and consumers would benefit from guiding standards on device quality and data formats. To address this growing need, we convened a virtual panel of industry and academic stakeholders, and this manuscript summarizes the outcomes of the discussion. Our objectives were to identify (1) key facilitators of and barriers to participation by CSFW manufacturers in guiding standards and (2) stakeholder priorities. The venues were the Yale Center for Biomedical Data Science Digital Health Monthly Seminar Series (62 participants) and the New England Chapter of the American College of Sports Medicine Annual Meeting (59 participants). In the discussion, stakeholders outlined both facilitators of (e.g., commercial return on investment in device quality, lucrative research partnerships, and transparent and multilevel evaluation of device quality) and barriers (e.g., competitive advantage conflict, lack of flexibility in previously developed devices) to participation in guiding standards. There was general agreement to adopt Keadle et al.’s standard pathway for testing devices (i.e., benchtop, laboratory, field-based, implementation) without consensus on the prioritization of these steps. Overall, there was enthusiasm not to add prescriptive or regulatory steps, but instead create a networking hub that connects companies to consumers and researchers for flexible guidance navigating the heterogeneity, multi-tiered development, dynamicity, and nebulousness of the CSFW field. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
9 citations (Crossref) [2023-10-31] https://waseda.pure.elsevier.com/en/publications/establishing-a-global-standard-for-wearable-devices-in-sport-and- ; https://repository.up.ac.za/handle/2263/81930?show=full ; https://www.ncbi.nlm.nih.gov/pubmed/34468950 ; https://researchportal.northumbria.ac.uk/en/publications/establishing-a-global-standard-for-wearable-devices-in-sport-and- ; https://pubmed.ncbi.nlm.nih.gov/34468950/ ; https://link.springer.com/article/10.1007/s40279-021-01543-5
Keywords: Consensus; Exercise; Humans; Sports; Sports Medicine; United States; Wearable Electronic Devices; adult; article; consensus; consumer; data science; dept.hms; electronic device; exercise; female; human; human experiment; investment; major clinical study; male; sport; sports medicine